2016
DOI: 10.1021/acs.jcim.6b00029
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arrhythmic Medication Propafenone a Potential Drug for Alzheimer’s Disease Inhibiting Aggregation of Aβ: In Silico and in Vitro Studies

Abstract: Alzheimer's disease (AD) is the most common form of dementia caused by the formation of Aβ aggregates. So far, no effective medicine for the treatment of AD is available. Many efforts have been made to find effective medicine to cope with AD. Curcumin is a drug candidate for AD, being a potent anti-amyloidogenic compound, but the results of clinical trials for it were either negative or inclusive. In the present study, we took advantages from accumulated knowledge about curcumin and have screened out four comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 83 publications
(177 reference statements)
3
31
0
Order By: Relevance
“…Ngo and colleagues (2016) [83] studied the inhibitory properties of curcumin against amyloid-β. They screened out four compounds that have chemical and structural similarity with curcumin more than 80% from all FDA-approved oral drugs.…”
Section: Research On Curcumin and Cell Models Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Ngo and colleagues (2016) [83] studied the inhibitory properties of curcumin against amyloid-β. They screened out four compounds that have chemical and structural similarity with curcumin more than 80% from all FDA-approved oral drugs.…”
Section: Research On Curcumin and Cell Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Using all-atom molecular dynamics simulation and the free energy perturbation method they showed that among predicted compounds anti-arrhythmic medication propafenone shows the best anti-amyloidogenic activity. The in vitro experiment further revealed that it can inhibit amyloid-β aggregation and protect cells against amyloid-β induced cytotoxicity to almost the same extent as curcumin [83]. …”
Section: Research On Curcumin and Cell Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Although a few studies in the literature proposed the cavity formed by the two β-sheets and the turn as possible binding site for curcumin [24,25] and other compounds such as Orange-G [26] this site is never occupied by the ligands considered in the present study. However, small portions of CURke, EGCG, QUER and ROSM ligands occasionally can penetrate this cavity during the dynamic simulations runs, when they are interacting with the A(1-40) protofibril in the Over position.…”
Section: Putative Binding Sites and Binding Free Energiesmentioning
confidence: 77%
“…Atomistic computer simulations are well suited to provide molecular-level details of amyloid oligomer and fibril interactions with ligands, helping in the future development and characterization of druggable modalities [12]. Basically four aspects of the flavonoids-amyloid interaction have been studied by computational methods: 1) the effect of ligands on the conformational transitions of Aβ monomers from initial random coil or α-helix into β-sheet structures [13,14] and ligand-mediated conformational change on Aβ dimer [15] by means of Replica Exchange Molecular Dynamics (REMD) simulations; 2) the effect of ligands on the aggregation of Aβ (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) using Coarse-Grained 2 of 15 Simulations [16]; 3) effect of ligands on the conformation and stability of amyloid-beta mutants [17] by Molecular Dynamics (MD) simulations; 4) preferential binding sites of ligands and their effect on amyloid structure-dynamics [18] on Aβ fragments and full-length single Aβ protofilament [19][20][21][22][23][24][25] by means of Docking experiments, MD simulations and Free Energy calculations.…”
Section: Introductionmentioning
confidence: 99%
“…ephedrine, arylalkene) [16,17,18]. Propiophenone derivatives called propafenone are primarily known on their antiarrhythmic action, but they are also involved in treatment of many different diseases including lupus erythematosus, epilepsy, Alzheimer's disease, malaria, ebola, cancer [19][20][21][22][23][24][25]. In addition, recent studies have shown that analogs of propafenone exhibit antifungal activity [26].…”
Section: Introductionmentioning
confidence: 99%